Hispanic linguistics current issues and new directions - Morales-Front, Alfonso; Ferreira, Michael J.; Leow, Ronald P. (Ronald Philip), 1954-; Sanz, Cristina (Issues in Hispanic and Lusophone linguistics ;, 2020)
"This volume addresses a wide range of phenomena including intonation, restructuring, clitic climbing, aspectual structure, subject focus marking, code-switching, lenition, loanwords, and heritage learning that are central in Hispanic linguistics today. The authors approach these issues from a variety of recent theoretical approaches and innovative methodologies and make important contributions to our current understanding of language acquisition, theoretical and descriptive linguistics, and language contact. This collection of articles is a testimony to the breadth and degree of specialization of the scholarly interest in the field. The selection of refereed chapters included in this volume were originally presented at the 20th Hispanic Linguistics Symposium (HLS) hosted at Georgetown University, 2016. The book should be read with interest by scholars and graduate students hoping to gain insight into the issues currently debated in Hispanic Linguistics"--